DESIGNING FITRAH MONEY: A MAQASIDIC DISCOURSE - Sifat, Imtiaz Mohammad; Mohamad, Azhar (Bank Indonesia, 2018)
Academic efforts in concocting a plausible alternative to fiat regime often staggers given inherent constrictions of Islamic jurisprudence and economic technicalities. Despite passionate advocacy of Muslim scholars, the campaign for gold dinar and silver dirham runs into allegations of being simplistic, anachronistic, regressive, unnecessary, and sub-optimal. Shunning the popular Maqasidic and historical approaches in debunking these claims, this paper highlights the need for a return to basics, the default factory settings as designed by God, and trowels a fitrah approach in evaluating gold and silver. As such, we proffer an open-minded approach in formulating an Islamically congruent currency and decry obstinate fixation with gold and silver, which hardly serve the best interests of ummah.